The Impact of Work Discipline and Competency on Production Employees' Performance Indonesian - Dharliana Hardjowikarto; Misbak Misbak; Lia Yulia; Moh Muklis Sulaeman; Julia Verboeket (PT. BATARI EDU CALYA, 2024)
The dynamic landscape of the automotive industry positions organizations such as PT Adient Automotive Indonesia as strategic suppliers of essential spare parts. The sustainability and competitive advantage of such firms are largely determined by the performance and quality of their human resources. Maintaining consistent production outcomes requires continuous attention to employee competence and work discipline as key determinants of performance. This study aims to: (1) analyze the effect of competence on the performance of production employees at PT Adient Automotive Indonesia; (2) examine the influence of work discipline on employee performance; and (3) assess the simultaneous effect of competence and work discipline on employee performance. A quantitative approach was employed using a sample of 88 production employees. The findings indicate that competence has a positive and statistically significant effect on employee performance. Similarly, work discipline exerts a positive and significant influence on performance. Furthermore, competence and work discipline simultaneously have a substantial and significant effect on production employee performance. These results highlight the importance of adopting a comprehensive human resource management strategy that integrates competency development and disciplinary reinforcement to enhance organizational productivity.